2013
DOI: 10.1017/s0317167100014955
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Surveillance of Amyotrophic Lateral Sclerosis in Saguenay Region

Abstract: Abstract:Objectives:The Neuromuscular Registry of Saguenay-Lac-Saint-Jean (SLSJ), Québec, Canada was established for epidemiological surveillance of neuromuscular disorders including amyotrophic lateral sclerosis (ALS). The objectives of this study are to analyze the ALS clinical characteristics of the SLSJ population and to determine the incidence rate over time by five year periods since 1985.Methods:The Registry was validated by a review of the medical records maintained at the CSSS de Chicoutimi, the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Retrospective data on ALS incidence spanning at least 10 years are available from some geographic areas with conflicting results, indicating stability [12][13][14][15][16][17] or an increase. [18][19][20][21][22] These differences are likely to be related to the largely different methods of case ascertainment, the assessment of different periods, and the use of diverse diagnostic criteria. Besides the PARALS, the Irish ALS register, which is the only prospective epidemiologic register that has been constantly active for more than 10 years, reported an increase of ALS incidence in the 1996 to 2014 period, limited to patients older than 75 years and without evidence of a differential increase in the 2 sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data on ALS incidence spanning at least 10 years are available from some geographic areas with conflicting results, indicating stability [12][13][14][15][16][17] or an increase. [18][19][20][21][22] These differences are likely to be related to the largely different methods of case ascertainment, the assessment of different periods, and the use of diverse diagnostic criteria. Besides the PARALS, the Irish ALS register, which is the only prospective epidemiologic register that has been constantly active for more than 10 years, reported an increase of ALS incidence in the 1996 to 2014 period, limited to patients older than 75 years and without evidence of a differential increase in the 2 sexes.…”
Section: Discussionmentioning
confidence: 99%
“…They found a rate of 3.01 per 100,000 per year for the five-year window-second only in quantity and timing to the BC data. 30 It could be that more recent measurements of ALS numbers reflect a time of greater incidence or better case ascertainment. In the present study, as highlighted in the Supplemental Data, incidence increases each year from 2010 through to 2014 and then decreases during 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for why BC numbers are more substantial could merely be reflective of the window of time in which they were measured. The closest window of Canadian data studied comes from a Quebec regional study 30 where 2005-2009 disease incidence was captured. They found a rate of 3.01 per 100,000 per year for the five-year window—second only in quantity and timing to the BC data 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The study in the current issue by Lareau-Trudel et al describes epidemiologic surveillance of ALS in the Saguenay-Lac-St-Jean region of Quebec (SLSG) 4 . The authors report similar clinical features of ALS to those observed in the literature, but they also report a significant increase in incidence rate of ALS among the > 65 years-old group between the 1985-2004 and the 2005-2009 periods.…”
Section: Editorialmentioning
confidence: 99%